Detection and Evaluation of metals in soil under influence of mining by Dispersive Energy X-ray Fluorescence Spectrometry (EDXRF), Lavras do Sul/RS - Gomes, Cristiane Heredia; Sperandio, Diogo Gabriel; Dessart, Rafael Lima; Giusti, Dionatan Daniel (Ciência e Natura, 2018)
Rocks are the primary source of chemical elements found in the earth. Among them metallic elements, which are distributed in most natural environments and their distribution in soils is widespread. Knowledge of the soil chemical composition will provide subsidies for a prediction of phytotoxicity and possible groundwater contamination. Concentrations of metals, in the right quantities, are essential for maintaining life. Although, if in high quantities (toxicity), can cause damage to plants, animals, and humans. This work consists of a chemical analysis of soil samples in the region of Lavras do Sul / RS, where mineral deposits occur. Until the year 1981 mining activities occupied the area without municipality, resulting in ore and waste deposits at inappropriate places, generating environmental liabilities, contributing to soil chemistry, and consequently affecting public health. Through the energy dispersive X-ray fluorescence spectrometry (EDXRF) method, 20 soil samples were analyzed in two profiles surrounding the municipality. Among them, high concentrations of Zn, Cu, Ce and Cd were detected, possibly contributing to anthropic activities and seasonal fluctuations.